THE EFFECT OF GROWTH ON THE ADEQUACY OF DEPRECIATION ALLOWANCES. - Kaufman, Felix; Gleason, Alan (The Accounting Review, 1953)
Abstract The article highlights that a recent issue of The American Economic Review contained an article challenging the widely held view that depreciation allowances necessarily fail to cover replacement costs during a period of rising prices. This view, it is argued, ignores the effects of physical asset expansion. The present article demonstrates by mathematical techniques that physical growth, by itself, would cause depreciation allowances to exceed replacement costs. It is possible, therefore, that the effect of rising prices on replacement costs may be completely offset by the effect of growth on depreciation allowances. The intention of the article is to demonstrate and analyze these propositions through three arithmetic models and to develop the implications of this analysis. The first model is designed solely to illustrate the effects of physical asset expansion on the relationship between depreciation charges and replacement costs. In the interests of clarity, certain simplifying assumptions are made. They are not essential, however, to the validity of the principles being demonstrated. Two other models will show the effects of altering some of these assumptions.